The Effect of Workload and Work Stress on the Performance of Teachers of SMK Kr. Pelangi Makale in Tana Toraja - Nugraha Putra Arrung; Ocky Sundari Rahardjo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to provide benefits and contributions in the form of additional insight/views in the field of management, especially in analyzing the effect of workload and work stress on the performance of teachers at SMK Kr. Pelangi Makale in Tana Toraja. And also this research is expected to provide new input and discourse in improving teacher performance by knowing and following up on workload and work stress problems experienced by teachers, and in the future can help in improving human resources in general and especially in educational institutions. The type of research used in this study is a quantitative descriptive analysis approach, namely by collecting data through questionnaires to describe the bond between the independent variables in the form of workload and work stress with the dependent variable, namely teacher performance where the object of research is taken at SMK Kr. Pelangi Makale in Tana Toraja. In the results of the measurement of work stress, the average value is included in the medium category. If it is related to Robbins's (2008) statement, the medium category in measuring work stress is included in the optimum level of stress. Where at this level having the right amount of stress can spur a person to have enthusiasm in dealing with problems, so that this attitude creates a sense of satisfaction with the work performance achieved is good. So the results of this study show that if work stress is added, then performance will also increase.